The Role of Serum (Eotaxin-3) Related with Patients of Allergic Diseases from Iraqi Grain Silos Workers Who Had a Positive Result of Total IgE - Al Khayali, B.D.H.; J. Muhammed, Haidar (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Through the identification of positive total IgE assay results in the serum and the estimation of Eotaxin-3 levels, this study sought to assess the role of (Eotaxin-3) in patients with allergic diseases from Silos workers. . The majority of Silos employees reported having similar symptoms, including red or itchy eyes, headache pain, cough, wheezing, nasal congestion, poor sense of smell, hives or swelling, shortness of breath, itchy or runny nose, frequent colds, frequent diarrhea, hoarse voice, or allergic asthma, allergic rhinitis, conjunctivitis, eosinophilia, and hyper eosinophilia syndrome. In this work, we showed that eotaxin-3 has a significant role in the pathogenicity of individuals with allergic illnesses in Silos who had elevated serum levels of total immunoglobulin E. One hundred and twenty subjects (eighty allergy patients and forty seemingly healthy controls) were used in the study to test the levels of Eotaxin-3 and Total IgE in the serum of the allergic patients as well as the control group. Using a VIDAS equipment, VIDAS®TOTAL IgE (IGE), Marcy-l' Etoile, France, the blood samples were utilized to estimate the serum total immunoglobulin-E (IgE) ratio. Blood Eotaxin-3 was also estimated. The ELISA MELSIN/China method quantitatively detects the Eotaxin-3 marker in patient serum and control serum. The results indicated that patients with allergic diseases had much higher concentrations of both IgE and Eotaxin-3 in their serum than did healthy controls (p<0.001). Additionally, there was no correlation between the levels of IgE and Eotaxin-3 in patients' serum; the correlation coefficient (r) between the two markers was = -0.06, and the level of significance was 0.642 (non-significant).